Production of grease from waste cooking oil - Norasmah, Othman (2009)
Vegetable oils have significant potential as a base fluid and a substitute for mineral oil for grease formulation. The objective of this research is to produce grease from waste cooking oil via saponification of a stearic acid with a lithium hydroxide monohydrate, LiOH. In this research, preparation and formulation of bio-based grease and determination of optimum operating condition were studied. The produced bio-based grease is expected to have better performance, and apply in variety industry such as agriculture/farming, forestry applications and food processing. The stearic acid, lithium hydroxide monohydrate and waste cooking oil compositions were manipulated in this research. The operating temperature and mixing period were also studied. The characteristics of produced grease were analyzed in order to evaluate the performance of the grease. Among parameters analyzed were depth penetration test, dropping point and oxidation stability. While grease hardness was determined using depth penetration test, and their oxidative stabilities was determined using copper corrosion test. The dropping point temperature was tested using dropping point apparatus. Results indicate that the lithium hydroxide monohydrate, stearic acid and waste cooking oil content significantly affect grease hardness, oxidative stability and dropping point temperature. NLGI 2 (common grease) grease was formulated in this study with optimum condition.